2020
DOI: 10.21203/rs.3.rs-73528/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microglial Activation Contributes to Cognitive Impairments in Rotenone-induced Mouse Parkinson’s Disease Model

Abstract: BackgroundCognitive decline occurs frequently in Parkinson’s disease (PD), which greatly decreases the life quality of patients. However, the mechanisms remain to be investigated. Neuroinflammation mediated by over-activated microglia is a common pathological feature in multiple neurological disorders, including PD. This study is designed to explore the role of microglia in cognitive deficits by using rotenone-induced mouse PD model. Methods: To evaluate the role of microglia in rotenone-induced cognitive defi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Additionally, persistently activated microglia have been shown to promote cognitive dysfunction in both infectious and sterile models of neuroinflammation (Vasek et al, 2016;Di Filippo et al, 2016;Zhang et al, 2021). These pieces of information, coupled with our observation that microglia are a primary target for MHV infection in the CNS (Figure 1I), led to the hypothesis that agerelated alterations in the microglial response may contribute to the spatial learning impairment 2).…”
Section: Aged Animals Have Increased Microglial Activation Following ...mentioning
confidence: 61%
“…Additionally, persistently activated microglia have been shown to promote cognitive dysfunction in both infectious and sterile models of neuroinflammation (Vasek et al, 2016;Di Filippo et al, 2016;Zhang et al, 2021). These pieces of information, coupled with our observation that microglia are a primary target for MHV infection in the CNS (Figure 1I), led to the hypothesis that agerelated alterations in the microglial response may contribute to the spatial learning impairment 2).…”
Section: Aged Animals Have Increased Microglial Activation Following ...mentioning
confidence: 61%
“…These activities have been shown to be involved in the mechanism of cognitive impairment and causes neurobehavioral changes (anxiety and anhedonia). [39][40][41] Additionally, studies have shown that peripheral mononuclear cell or bone-marrow derived microglia, infiltrate the brain parenchyma after psychological stress, and further leads to neuroinflammation, anxiety and memory deficit. 42 Taken together, this suggests that social stress promotes peripheral immune cell infiltration regardless of genotype, but more so in sickle cell which is already a pro-inflammatory state.…”
Section: Discussionmentioning
confidence: 99%
“…Neuroinflammation is critically involved in the pathophysiology of acute injuries and diseases (including aging and neurodegeneration) in the central nervous system (CNS) [ 1 , 2 , 3 , 4 ]. Profound inflammatory responses are characterized by the activation of glial cells, which are primary innate immune cells of the CNS.…”
Section: Prefacementioning
confidence: 99%